What's 'evangelical' got to do with it? Disentangling the impact of evangelical Protestantism on environmental outcomes. Issue 2 (4th March 2018) - Smith, E. Keith; Hempel, Lynn M.; MacIlroy, Kelsea
ABSTRACT: Empirical research on the relationship between evangelical Protestants and the environment has generated a range of divergent findings. Measurements of evangelical Protestants vary greatly, as do the dependent environmental outcomes they are used to predict. Serious questions remain concerning when and how 'evangelicals' diverge from others in their environmental views and behaviors. Here, two foundational questions concerning the relationship between evangelical Protestants and the environment are explored. First, do religious effects differ based on how evangelicals are defined and measured? Second, does the relationship vary with the outcome variable used? Utilizing 14 dependent variables from two nationally representative data sets, among the measures of evangelical Protestantism, biblical literalism is the most important predictor of environmental outcomes. Negative religious effects are more pronounced when questions concern future environmental outcomes, but not current environmental concerns, and when outcomes are related to collective actions rather than individual ones.